PENGEMBANGAN KEBERAGAMAAN PESERTA DIDIK MELALUI BUDAYA AGAMA DI SMPN 10 BANDUNG - Ulfah Azqia Mupidah; Nani Rohaeni; Taufikurohman (STAI Pelabuhan Ratu, 2021)
The purpose of the study was to describe the religious development student trought the development of religious culture at SMP Negeri 10 Bandung. The result of the study showed that the implementation of coaching student’s religious through the development of religious culture at SMP Negeri 10 Bandung has been going well and programmed, both conducted by the school as an educational institution that is intact with the wisdom which relate to the development of the religious culture in school and community activities undertaken by Rohis (The Spiritual of Islam) as a kind of special school extracurricular activities shade other religious activities. This success can be achieved due to the efforts of the principal and the support of the entire school community by showing commitment each of which takes place together and support each other